But, what do they need? A user-centred approach to Generative Artificial Intelligence literacies in an academic library - Dumbell, Petra; Taylor, Amy; Hulcup, Claire (Journal of Academic Language and Learning, 2026)
As Generative Artificial Intelligence (Gen-AI) is transforming learning and teaching in higher education, the Library has taken a leading role in supporting students’ AI literacies at Curtin University. Early workshops revealed a mismatch between content and student needs, prompting a user experience survey that uncovered confusion, fear and uncertainty. We found that teaching Gen-AI requires flexibility, critical thinking, and a shift from traditional approaches – which starts by listening to our learners. As Gen-AI technologies and institutional policies change, our approach to learning and teaching AI literacies must be adaptable, student-centred, and open to uncertainty and discovery.